1999
DOI: 10.1126/science.285.5424.88
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Quasi-Particle Scattering Resonances in Bi 2 Sr 2 CaCu 2 O 8+δ

Abstract: Low-temperature scanning tunneling spectroscopy of the high transition temperature (high-Tc) cuprate Bi2Sr2CaCu2O8+delta reveals the existence of large numbers of identical regions with diameters of about 3 nanometers that have a relatively high density of low-energy quasi-particle states. Their spatial and spectroscopic characteristics are consistent with theories of strong quasi-particle scattering from atomic-scale impurities in a d-wave superconductor. These characteristics include breaking of local partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
148
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(167 citation statements)
references
References 24 publications
17
148
0
Order By: Relevance
“…As was shown by Pan et al [4] a nonmagnetic impurity as Zn locally destroys the superconductivity, as indicated by the absence of a hole-like resonance. Nevertheless a particle-like resonance is observed, due to the depletion of states near the Fermi level, which we attribute to the pseudo-gap.…”
Section: Instituto De Física Gleb Wataghin Universidade Estadual De mentioning
confidence: 79%
See 3 more Smart Citations
“…As was shown by Pan et al [4] a nonmagnetic impurity as Zn locally destroys the superconductivity, as indicated by the absence of a hole-like resonance. Nevertheless a particle-like resonance is observed, due to the depletion of states near the Fermi level, which we attribute to the pseudo-gap.…”
Section: Instituto De Física Gleb Wataghin Universidade Estadual De mentioning
confidence: 79%
“…As various different theoretical proposals for the pseudo-gap have been put forward the need of experimental probes that are able to distinguish between them is of great interest. Here we argue that scanning tunneling microscopy (STM) experiments in underdoped HTSC, that serve as a local probe of impurity states [4,5], can be used in order to differentiate between at least two classes of proposals.…”
Section: Instituto De Física Gleb Wataghin Universidade Estadual De mentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of a superconductor, the method can potentially distinguish the nature of the scattering by a particular impurity. PACS numbers: 74.55.+v,72.10.Fk,73.20.At,74.72.ah Scanning Tunneling Microscopy (STM), which measures the "local density of states" (LDOS) as a function of position and energy set by the bias voltage, has opened the door to imaging the sub-nanoscale topography and electronic structure of materials, including normal metals [1] and especially cuprate superconductors [2,3,4,5,6,7,8,9].The dispersion relations of (Landau or Bogoliubov) quasiparticles may be extracted from STM data on normal metals [10,11] and superconductors [13], via the inverse method called Fourier transform scanning tunneling spectroscopy (FT-STS) [10,13], or directly in real space [11]. This technique is based on the fact that impurities produce spatial modulations of the LDOS in their vicinity -standing waves in the electronic structure that generalize the Friedel oscillations found in metals at the Fermi energy.…”
mentioning
confidence: 99%